La influencia de las fuentes de información externas en el valor de marca: una perspectiva desde el joven consumidor - Bravo Gil, Rafael (Cuadernos de Estudios Empresariales, 2006)
Brand information provided by external agents has different effects on the consumer depending on its origin. The purpose of this study is to analyse the effects of different information sources: advertising, family and peers in the formation of brand equity. Thus, an empirical study has been conducted in order to analyse these effects on the specific case of young adults leaving their family home. Overall, results show that information has a positive effect on dimensions of brand equity. However, these effects are higher when the source of information is the family or peers than in the case of advertising.